Curriculum and Learning Management: Integration With Creative Economy Values in Improving Students' Life Skills - Andhika Putra Widyadharma; Ikhsan Gunadi; Mohtar Kamisi; Yes Matheos Lasarus Malaikosa (Soegijapranata Catholic University, 2021)
A curriculum is an important unit in the learning process as guidance for teachers in managing learning activities both inside and outside the classroom. Since vocational education has the function of preparing the workforce, they are required to produce graduates as the demands of the working world. The manpower needed is human resources who have the competence and skills under their field of work, high adaptability, as well as competitiveness. Previous studies have found that the curriculum is developed according to the demands of the working world and to anticipate developments in science and technology. Schools also involved creative actors in learning activities, intended to integrate various creative activities in the curriculum, especially in the C3 component of expertise competencies in the substance or teaching materials. Learning at SMK Grafika Desa Putera is presented in various competencies by integrating the important value of the creative economy for students. The learning model is presented and organized into normative, adaptive, productive, local content, and self-development programs to produce productive creative work. It can be concluded that the implementation of creative economy education aims to foster positive (creative) character, attitudes, and behavior as a form of realization of the Ministry Regulation No. 32/2013 concerning National Education Standards mandating that the learning process are required to be carried out actively, creatively, innovatively, and student-centered